Pre-Service Physics Teachers’ Knowledge and Perceptions of the Green Laboratory as an Education for Sustainable Development Implementation to Address Generation Z Character Challenges - Sasva Vannes Farawasi (FKIP - Universitas Riau, 2026)
Education for Sustainable Development (ESD) emphasizes the integration of knowledge, skills, and character values through meaningful learning experiences. This study examined the knowledge and perceptions of pre-service physics teachers regarding the Green Laboratory as an ESD implementation to address Generation Z character challenges. Using a descriptive quantitative approach, 30 undergraduate students from the Physics Education program at Universitas Mulawarman completed validated questionnaires on Green Laboratory principles and Generation Z character indicators. Results revealed high knowledge levels across all indicators: environmental responsibility (95.1%), waste management (91.7%), and resource efficiency (86.8%). Pre-service teachers also demonstrated very positive perceptions of the Green Laboratory's role in developing responsibility (90.6%), discipline (90.6%), and environmental awareness (89.2%). These findings indicate that the Green Laboratory is perceived as an effective strategy for integrating ESD values and character development in physics teacher education, offering practical implications for curriculum design in teacher preparation programs.